Sztuka i dobór naturalny - Dutton, Denis (Kultura-Społeczeństwo-Edukacja, 2015)
The relation between art and the idea of natural selection makes the key issue of this paper. The author examines how Charles Darwin's conc ept of evolution might have affected the sphere of aesthetics. However, the author arguments against understanding of art as a side product of human progress and takes it as an independent form of human agency. The critique of various evolutionary standpoints laid out in this article holds to the standpoint that we cannot recreate with other means the moments of pleasure delivered by art. Thus it is extremely important to understand art as a form of human creativity and a neces sary part of our existence beyond biological determinism stressed out by many evolutionary thinkers.